Evaluation of the synergistic change in cultivated land and wetland in northeast China from 1990 to 2035 - Mengjing Li; Wei Ye; Ya-juan Li; Chenfeng Cui (Scientific Reports)
Abstract Wetlands are the most biodiverse ecological landscape in nature and one of the most important natural resources for human beings. In recent years, wetlands in northeast China have been increasingly converted into cultivated land, resulting in significant reduction in wetland area. Currently, the extensive and prolonged use of natural resources, combined with mismanagement and climate change, presents considerable challenges for both governments and future sustainability. This study utilized the PLUS model to analyze the spatial-temporal transformation of cultivated land and wetland in northeast China over the past 30 years and to project land use changes from 2020 to 2035. The analysis quantitatively evaluated the impacts of human activities and climate change. The results showed that: (1) Wetlands in northeast China have been progressively converted into paddy fields or degraded into unused land. (2) Topography, GDP, and temperature are the primary drivers of land use change over the past three decades. (3) There is an urgent need for national macro-policy regulation to mitigate the degradation of cultivated land and wetlands through the rational allocation of land resources.